Analysis of airborne germ concentrations and Covid 19 transmission at Port Health Office of Semarang - Dewi Windy Cintya; Raharjo Mursid (E3S Web of Conferences, 2025)
Covid 19 as a new emerging disease has spread all over the world. Covid 19 case also occurred at Port Health Office of Semarang, where the number of Covid 19 cases was 71 of 126 employees (56% percentage) and the airborne germ rate in preliminary study exceeded the standard set by American Conference of Governmental Industrial Hygienist (ACGIH) which was 500 CFU/m3. The purpose of analyzing the number of airborne germs with the incidence of Covid 19 cases at KKP Semarang. This study is an observational study by measuring the physical quality of the air in the research location and taking air samples to calculate the number of germs in the air in the room. The results of this study that the number of airborne germs is influenced by factors such as temperature, humidity, and lighting. The use of ventilation systems (using air conditioning or fans) will also affect the development of microorganisms in the room. Efforts have been made to control the development of airborne germs in the room, including the placement of a humidifier, maintenance of air conditioners/fans, and the obligation to use PPE (masks) in the room to minimize the transmission of Covid 19 during activities.